The Impact of COVID on Lower-Limb Exoskeleton Robotic System Patents—A Review - Cristina Floriana Pană; Virginia Maria Rădulescu; Daniela Maria Pătrașcu-Pană; Florina Luminița Petcu (Besnea); Ionuț Cristian Reșceanu; Ștefan Irinel Cismaru; Andrei Trășculescu; Nicu Bîzdoacă (Applied Sciences, 2022)
In recent decades, the field of physical rehabilitation, with the help of robotic systems that aid the population of any age with locomotor difficulties, has been evolving rapidly. Several robotic exoskeleton systems of the lower limbs have been proposed in the patent literature and some are even commercially available. Given the above, we are asking ourselves at the end of the COVID-19 pandemic: how much has this pandemic affected both the publication of patents and the application of new ones? How has new patents’ publication volume or application in robotic exoskeleton systems changed? We hypothesize that this pandemic has caused a reduction in the volume of new applications and possibly publications. We compare pandemic analysis and the last decade’s analysis to answer these questions. In this study, we used a set of statistical tests to see if there were any statistically significant changes. Our results show that the pandemic had at least one effect on applying for new patents based on the information analyzed from the three databases examined.